Identifying speculative demand shocks in commodity futures markets through changes in volatility - Michael Hachula; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper studies the effects of financial speculation on commodity futures returns, using publicly available data from the US Commodity Futures Trading Commission, aggregated by trader groups. We exploit the heteroskedasticity in the weekly data to identify exogenous variation in speculators' positions. The results suggest that idiosyncratic net long demand shocks of both index investors and hedge funds increase futures returns. They further indicate that these shocks are a relevant driver of returns, especially during periods of high speculative demand volatility. These findings confirm significant price effects of financial investments, complementing existing evidence based on disaggregated and proprietary daily data.
Keywords: Q02; G13; E39; 330; financialization; hedge funds; index investors; market structure; liquidity; limits to arbitrage; heteroskedasticity